The Issue of Complicity with a Non-Identified Person in Lithuanian Case Law - Skripkutė, Greta (Teisė, 2020)
The article aims to reveal the issues of complicity with an unidentified person and to analyze the peculiarities of the application of this institute in the practise of the courts of all levels after the plenary session of the Supreme Court of Lithuania on January 6, 2009 when the position was formed. The issues include assumptions based on court decisions, a possible breach of the presumption of innocence against an unidentified person, and the principle of the inevitability of criminal liability is also discussed. The analysis highlighted the incompatibility of some court decisions with the provisions of criminal law, the importance of the wording used by courts and pre-trial officers, prosecutors for the presumption of innocence, and the need to maintain a balance when convicting an identified accused who was associated with an unidentified person.